2017
DOI: 10.3892/mmr.2017.6141
|View full text |Cite
|
Sign up to set email alerts
|

ATM participates in the regulation of viability and cell cycle via ellipticine in bladder cancer

Abstract: Ellipticine, an alkaloid isolated from Apocyanaceae plants, has been demonstrated to exhibit antitumor activity in several cancers. However, the effect and the mechanisms underlying its action have not been investigated in human bladder cancer cells. The aim of the present study was to investigate the effect and mechanism of ellipticine on the behavior of T-24 bladder cancer cells. T-24 cells were treated with varying concentrations and durations of ellipticine. Cell viability was evaluated by Cell Counting Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Our findings showed that most of the cells were significantly arrested on the phase S, upon Br-Ell-SO 3 Na treatment at both 35 µM and 70 µM doses. As mentioned earlier, the anticancer potential of ellipticine and its derivatives has already been reported elsewhere, but usually those substances induce the cell arrest at the phase G2 of the cell cycle [26][27][28]. Our data demonstrated that the mechanism of action of Br-Ell-SO 3 Na on the cell cycle differs from previously reported ellipticine derivatives.…”
Section: Discussionsupporting
confidence: 71%
“…Our findings showed that most of the cells were significantly arrested on the phase S, upon Br-Ell-SO 3 Na treatment at both 35 µM and 70 µM doses. As mentioned earlier, the anticancer potential of ellipticine and its derivatives has already been reported elsewhere, but usually those substances induce the cell arrest at the phase G2 of the cell cycle [26][27][28]. Our data demonstrated that the mechanism of action of Br-Ell-SO 3 Na on the cell cycle differs from previously reported ellipticine derivatives.…”
Section: Discussionsupporting
confidence: 71%
“…The tumor suppressor p53 plays an essential role in many malignancies, including promoting progression of BCa [ 99 , 100 , 101 , 102 ]. Dueñas et al found that mutations in the TP53 gene and epigenetically mediated increased p53 protein expression favor the progression and recurrence of non-muscle invasive bladder cancer (NMIBC).…”
Section: Discussionmentioning
confidence: 99%
“…Biological pathways of four significant modules from PPI network analysis using Cytoscape contained "cell cycle, mitotic", "epithelial to mesenchymal transition" (EMT), "ErbB receptor signaling" and "neuronal system" (Figure 3). Of note, "cell cycle" and "p53 signaling pathways" directly modulate the cell cycle in many cancers, and are an inevitable theme in cancer research [38,39]. Tumor suppressor p53 is the most frequently mutated gene in human cancer [40].…”
Section: Biological Progression Potentially Associated With Bcamentioning
confidence: 99%